Kewenangan Bawaslu Kabupaten/Kota dalam Proses Penanganan Pelanggaran Kode Etik Pengawasan Pemilihan Umum Ad Hoc - Idhar Idhar; Siti Hasanah; Firzhal Arzhi Jiwantara (Utan Kayu Publishing, 2023)
The authority of regency-city Bawaslu is contained in Election Supervisory Body Regulation Number 4 of 201 concerning Mechanisms for Handling Violations of the Ad Hoc Election Supervisory Committee's Code of Ethics, whereby regency-municipality Bawaslu becomes a judge in the ethical judicial process whose professional integrity must be demonstrated so that the ethical court previously conducted by DKPP is maintained as an effort to uphold democracy from deviant administrative practices.